Phytotoxicity Evolution of Biowastes Undergoing Aerobic Decomposition. (28th April 2013) - Soares, M. R.; Matsinhe, C.; Belo, S.; Quina, M. J.; Quinta-Ferreira, R.
Abstract : This study is mainly focused on the phytotoxicity improvement within five to six weeks of thermophilic composting of biowastes. Two sets of experiments were conducted involving both sawdust and rice husk as bulking agents, which were composted in self-heating reactors with potato-peel industrial waste and grass clippings as organic materials. The main variables observed over time were temperature, oxygen uptake rate (OUR), biodegradability, and germination index (GI). The effects of compost water extracts on seed germination and primary root growth of garden cress ( Lepidium sativum ) were measured to calculate the germination index (GI). The biodegradability was well assessed by measuring lignin content, using the Klason method. The experimental results showed that initial compositions strongly determined the profiles of phytotoxicity and the period of maturation. The phytotoxicity assessment in the experiments with sawdust revealed that after 39 days of composting, the GI attained the maximum value of 30%, but using rice husk, it was possible to reach 70% in the same period of time. Our findings showed that, at a certain point, higher cumulative OUR led to lower germination index, and proportional relationship between the cumulative OUR and GI was observed, after thermophilic phase.